Incidencia de la NIC 16: propiedad, planta y equipo para el control de los activos fijos en las empresas ubicadas en el parque industrial norte del D.M.Q. - Cifuentes Callay, Ana Cristina (2017)
The subject of the following research is to get to know the incidences that have been generated around the companies located at Park Industrial in the North side of Distrito Metropolitan de Quito – DMQ, due to the application of NIC 16: Property, Plant and equipment. Therefore, the Park Industrial de Itulcachi located at the kilometer 4, 8 on the way Pifo – Pintag; and the Zone Industrial of Calacalí located around kilometer 17 next to La Mitad Del Mundo have been visited. With the final purpose to get to know the story, specific characteristics and the companies operating at the industrial zone. In order to know the incidences caused in such companies we performed the NIC16 analysis in property, plant and equipment. Within the accounting standard we found: Recognition of an active as Property, Plant and Equipment, The susceptibility of measurement, variation and reevaluation, And also, the probability that the entity obtains the future economic benefits derived there from. The actives cost can be reliably valued. The accounting record date. The form of acquisition (paid cash or financed), installments plus interest and costs- general expenses, that under this rule could be taken as part of the real estate. The measurement after the recognition of fixed assets. Segmented depreciation of fixed assets. Deterioration and compensation of the asset, which owns an entity to be used in the production or supply of estate and services, or for administration purposes; which are expected to be used during a period of more than one year. In order to know the incidence generated a survey was realized to the companies located at the Zones Industrial at the North Side of DMQ after this analysis. We found out that most of the organizations are based on the regulations. We also performed an analysis of the balances generated by the companies that were studied, where we could observe that the fundamental incidents of these rules are the most real presentation of the financial situation of this item